The awareness of the international veterinary profession of evidence-based veterinary medicine and preferred methods of training - Huntley, Selene J.; Dean, Rachel S.; Brennan, Marnie L. (MDPI, 2017)
Evidence-based veterinary medicine (EVM) is an evolving discipline in veterinary medicine so it is important to periodically “benchmark” opinion about EVM across the profession. An international survey to assess veterinarians’ awareness of EVM was conducted. Veterinarians were surveyed via an online questionnaire (all countries) or a postal questionnaire (UK only). Participants were asked whether they had heard of EVM, where they had first heard the term, and their preferences of method for receiving continuing professional development (CPD). There were 6310 respondents, of which 4579 (72.5%) worked in the UK and 5384 (85.3%) were clinicians. Veterinarians that had heard of EVM (n = 5420, 85.9%) were most likely to be clinicians (OR = 4.00; 95% CI: 3.37, 4.75), respondents working in the UK (OR = 1.32; CI: 1.13, 1.54), or respondents with a postgraduate degree or qualification (OR = 1.77; CI: 1.51, 2.08). The most common sources from which respondents had heard of EVM were at vet school or university (n = 1207, 29.8%), via literature (peer-reviewed papers or other publications) (n = 1074, 26.5%), and via CPD courses (n = 564, 13.9%). Most respondents were interested in finding out more about EVM (n = 4256 of 6173, 69%). The preferred methods of CPD were day or evening seminars (n = 2992 of 6017, 49.7%), conferences (n = 1409, 23.4%), and online courses (n = 524, 8.7%), although the order of preference differed slightly between groups. There appears to be substantial awareness of EVM amongst veterinarians internationally. However, it appears that further training in EVM would be welcomed. Preferences on how CPD in general is received differs between groups, so this should be borne in mind by training providers when formulating a strategy for the dissemination of EVM training across the global profession.